2020
DOI: 10.3389/fimmu.2020.01456
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells and T Cells, Partners in Atherogenesis and the Translating Road Ahead

Abstract: Atherosclerosis is a chronic process associated with arterial inflammation, the accumulation of lipids, plaque formation in vessel walls, and thrombosis with late mortal complications such as myocardial infarction and ischemic stroke. Immune and inflammatory responses have significant effects on every phase of atherosclerosis. Increasing evidence has shown that both innate and adaptive "arms" of the immune system play important roles in regulating the progression of atherosclerosis. Accumulating evidence sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 196 publications
(249 reference statements)
0
26
0
Order By: Relevance
“…A previous study reported that a lack of DCs in mice could significantly reverse the progression of atherosclerotic plaques (Durpes et al 2015). In further exploration of the subsets of DCs (Sun et al 2020), it was found that CD11b + DC (Stoneman et al 2007;Busch et al 2014;Gao et al 2016;Rombouts et al 2016) and CCL17 + DC (Rader and Daugherty, 2008;Weber et al 2011) subsets have the effect of promoting atherosclerosis, and further exploration under more experimental conditions will provide multi-dimensional evidence. Whether CD103 + DCs (Choi et al 2011;Li et al 2017;Clement et al 2018) and plasmacytoid DCs (Daissormont et al 2011;Macritchie et al 2012) play pro-atherosclerotic or anti-atherosclerotic roles is controversial, which may depend on animal strains, different pathological models and other conditions.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study reported that a lack of DCs in mice could significantly reverse the progression of atherosclerotic plaques (Durpes et al 2015). In further exploration of the subsets of DCs (Sun et al 2020), it was found that CD11b + DC (Stoneman et al 2007;Busch et al 2014;Gao et al 2016;Rombouts et al 2016) and CCL17 + DC (Rader and Daugherty, 2008;Weber et al 2011) subsets have the effect of promoting atherosclerosis, and further exploration under more experimental conditions will provide multi-dimensional evidence. Whether CD103 + DCs (Choi et al 2011;Li et al 2017;Clement et al 2018) and plasmacytoid DCs (Daissormont et al 2011;Macritchie et al 2012) play pro-atherosclerotic or anti-atherosclerotic roles is controversial, which may depend on animal strains, different pathological models and other conditions.…”
Section: Discussionmentioning
confidence: 97%
“…T cells expressing the surface marker of CD8 are involved in the recognition of antigens expressed by the major histocompatibility complex (MHC) class I. CD8 + T cells kill the target cells by triggering apoptosis in the target cells. 81 Several chemokines released in the atherosclerotic lesion milieu are involved in the recruitment of the CD8 + T cells, which may then stimulate apoptosis in other immune cells and VSMCs, resulting in the development of lesions and related adverse complications. 82 , 83 One of the functions of the natural killer (NK) T (NKT) cells is to recognize lipid antigens presented by CD1 molecules on several cells.…”
Section: Innate and Adaptive Immunity In Atherosclerosismentioning
confidence: 99%
“…In line with the observed gene expression profile of cluster 1, the GO term enrichment analysis revealed signaling pathways linked to T-cell activation, the positive regulation of cell adhesion, cytokine production, cell-to-cell adhesion, and leukocyte migration, as well as antigen processing and presentation via MHC class II (Figure S4B). This indicates that cluster 1 is an important population involved in antigen presentation and T-cell activation in the atherosclerotic plaques [44]. Cluster 2 exhibited a gene expression profile of macrophages as shown by the expression of Ednrb, Fcna, Retnl, and Cd209f, as well as genes that are typical for resident macrophages (Lyve1 and FCGR1A (CD64)) [5] (Figures 2G and S3).…”
Section: Atherosclerosis Cluster Gene Expression Signaturesmentioning
confidence: 89%